Análisis de la utilización del entorno virtual de aprendizaje por parte de los docentes - García Calle, Diana Flor (2018)
The research carried out analyzes the use of the virtual learning environment (EVA) by the teachers of the Faculty of Agricultural Economics at the Agrarian University of Ecuador during the First Semester of 2016. For the data collection, a The 41 teachers who are part of the Faculty and the review of the EVA session to which each teacher has access. This allowed to know the use of the activities and resources of the EVA and the opinions of the teachers about their usefulness. The data show that although 78% of teachers consider the use of VAS to be useful for the teaching / learning process, only 12% indicate that VAS represents a fundamental element of this process. In addition, only 10% of teachers have their own initiative when using EVA and only 7% of teachers indicate that their ability to master this tool is excellent. In the review of the session for each teacher, it was confirmed that occasional teachers use the virtual environment more frequently in relation to appointment. The work identified identifies the need to train teachers in the proper use of EVA.